Optimization Position Variable Refrigerant Flow In Building Using CFD Method - Permatasari, Rosyida; Khairunisa , Riana (International Journal of Electrical, Energy and Power System Engineering, 2023)
Variable refrigerant flow type is a multi-split type air conditioner for multi-story buildings. The aim of this study getting obtains optimization placement of the condensing unit to inlet air temperature in a multi-story building using the CFD method. The simulation was conducted from the 11th to the 30th floor. There are three variations of condensing unit position on each floor (Variation 1), on every two floors (Variation 2), and on the roof (variation 3). The result of the first variation is 35.32 °C, with the difference between the highest and lowest is 3.9 °C. The average temperature of the 2nd variation is 34.44 °C, with the difference between the highest and lowest being 0.92 °C. The average temperature of the 3rd variation is 36.65 °C, with the difference between the highest and lowest being 8.03 °C. Among the three variations, the 2nd variation of the condensing unit input air temperature is lower. Then the difference between the highest and lowest temperatures is not too far apart, indicating a more even distribution of air. The 1st, 2nd, and 3rd variations condensing unit position do not exceed Panasonic VRF air conditioner operational temperature limit, which is 52 °C.